The Labor Productivity Gap between Formal Businesses Run by Women and Men. Issue 4 (1st October 2020) - Islam, Asif M.; Gaddis, Isis; Palacios López, Amparo; Amin, Mohammad
ABSTRACT: This study analyzes gender differences in labor productivity in the formal private sector, using data from 126 mostly developing economies. The results reveal a sizable unconditional gap, with labor productivity being approximately 11 percent lower among women- than men-managed firms. The analyses are based on women's management, which is more strongly associated with labor productivity than women's participation in ownership, which has been the focus of most previous studies. Decomposition techniques reveal several factors that contribute to lower labor productivity of women-managed firms relative to firms managed by men: Fewer women-managed firms protect themselves from crime and power outages, have their own websites, and are (co-)owned by foreigners. In addition, in the manufacturing sector, women-managed firms are less capitalized and have lower labor costs than firms managed by men.